# Thread: quick easy question im sure

1. ## quick easy question im sure

can someone explain to me how -y=-|x|+2 turns into y=|x|-2

2. Dear wonderd,

Multiply the whole equation by -1.

3. i dont understand, i do understand that to get the y by itself you divide by -1 but what are you suspose to do to the other side of the equal sign?
can someone explain how to divid -1 by -|x|+2 properly?

4. Originally Posted by wonderd
i dont understand, i do understand that to get the y by itself you divide by -1 but what are you suspose to do to the other side of the equal sign?
can someone explain how to divid -1 by -|x|+2 properly?
You divide each of the terms by -1:

$\frac{-|x|}{-1} = |x|$

$\frac{2}{-1} = -2$

Thus, you end up with $|x|-2$.

5. thank you

6. Or, as sudharaka said, multiply both sides of the equation by -1:
(-1)(-y)= (-1)(-|x|+ 2). The left is, of course, y and on the right you have (-1)(-|x|)+ (-1)(2)= |x|- 2.

7. Originally Posted by wonderd
can someone explain to me how -y=-|x|+2 turns into y=|x|-2
Hi wonderd,

you may add y to both sides

$-y=-|x|+2$

$y-y=y-|x|+2$

$0=y-|x|+2$

add |x| to both sides

$|x|=y+|x|-|x|+2$

$|x|=y+2$

subtract 2 from both sides

$|x|-2=y+2-2,\ |x|-2=y$

It's much quicker to multiply both sides by -1
or divide both sides by -1, but it helps to know how to juggle.